Is Montenegro Considered as a Sports-Recreational Destination? - Sanja Pekovic; Djurdjica Perovic; Tatjana Stanovcic; Jovana Vukcevic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The paper aims to examine if, according to the tourists coming to the country, Montenegro is considered as a sport-recreational destination. The data used in the study is extracted from the Montenegrin survey called Guest Survey 2014, comprising of 35 questions related to the tourist travel behavior and satisfaction during their stay in Montenegro. The paper uses the results of the study to provide descriptive statistics concerning the motives of tourist to visit Montenegro (one of the question is related to sport-recreational activities). Furthermore, it verifi es link between tourists' motivation related to sport -recreational activities to come to Montenegro and their overall satisfaction with sport -recreational activities. The results indicated that only around 1% of tourists in our sample who visited Montenegro indicated sport- recreational activities as the main motive for the visit, around 3% of tourists indicated sport- recreational activities as a second motive while around 5% of tourists indicated sport and recreational activities as the third motive. However, around 60% of tourists reported that they were satisfi ed with overall sport -recreational activities during their stay in Montenegro. This study shows that even that Montenegrin sport-recreational off er is on the satisfactory level, managers and policy-makers should provide additional eff ort to present Montenegro as a sport-recreational destination since very low percentage of tourists are motivated to visit Montenegro related to these activities. The paper thus concludes by setting recommendations related to diversifi cation of Montenegrin tourism off er by pursuing sports-recreational tourism forms.